Early Relief of Pruritus in Atopic Dermatitis with Crisaborole Ointment, A Non-steroidal, Phosphodiesterase 4 Inhibitor - Gil Yosipovitch; Linda F. Gold; Mark G. Lebwohl; Jonathan I. Silverberg; Anna M. Tallman; Lee T. Zane (Medical Journals Sweden, 2018)
Pruritus occurs in all patients with atopic dermatitis and requires quick relief to reduce disease exacerbation and improve quality of life. Crisaborole ointment is a non-steroidal phosphodiesterase 4 inhibitor for the treatment of mild-to-moderate atopic dermatitis. This post hoc analysis explores crisaborole ointment for early relief of pruritus in patients with mild to moderate atopic dermatitis from 2 phase III studies. Patients received crisaborole or vehicle twice daily for 28 days. Pruritus was graded on a 4-point scale of none (0) to severe (3). Early improvement in pruritus required a score of none (0) or mild (1), with a ≥ 1-grade improvement from baseline on day 6. Significantly more patients experienced early improvement in pruritus with crisaborole than with vehicle (56.6% vs 39.5%; p <0.001), including at earliest assessment (day 2, 34.3% vs 27.3%; p = 0.013). Crisaborole is a topical treatment option that can rapidly relieve atopic dermatitis-associated pruritus.